Fine-tuning the thicknesses of organic layers to realize high-efficiency and long-lifetime blue organic light-emitting diodes - 于建宁 张民艳 李崇 尚玉柱 吕燕芳 魏斌 黄维 (Chinese physics B, 2012)
By using p-bis（p - N, N-diphenyl-aminostyryl）benzene doped 2-tert-butyl-9, 10-bis-β-naphthyl）-anthracene as an emitting layer, we fabricate a high-efficiency and long-lifetime blue organic light emitting diode with a maximum external quantum efficiency of 6.19% and a stable lifetime at a high initial current density of 0.0375 A/cm2. We demonstrate that the change in the thicknesses of organic layers affects the operating voltage and luminous efficiency greater than the lifetime. The lifetime being independent of thickness is beneficial in achieving high-quality full-colour display devices and white lighting sources with multi-emitters.